A Visible‐Light‐Promoted C‐H Arylation and Heteroarylation of Uracil Derivatives with Diazoniums in Aqueous Conditions. Issue 6 (7th June 2022) - Liu, An‐Di; Wang, Zhao‐Li; Liu, Li; Cheng, Liang
Abstract: The photoredox synthesis of C‐5 (hetero)arylated uracil and uridine substrates with the corresponding diazonium salts is described. The coupling proceeds efficiently without protection of the hydroxyls at the ribose or pre‐functionalization of the C5 position at the nucleobase. No transition‐metal catalyst is used in this transformation, thereby avoiding metal contamination in the final products. The use of water as the medium also eliminates the impurities caused by the use of organic solvents. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of 5‐aryl and 5‐heteroaryl uracil derivatives Basic Protocol 2 : Synthesis of 5‐aryl uridine and deoxyuridine uridine derivatives